2017
DOI: 10.1108/ijlm-09-2015-0163
|View full text |Cite
|
Sign up to set email alerts
|

Appraisements of material handling system in context of fiscal and environment extent

Abstract: Purpose In present research, the authors conducted the massive literature review and collected the information, in regards to material handling system (MHS) to build a multi criteria MHS hierarchical module consists of ecological cum fiscal criteria. Moreover, similar literature review assisted the authors to resolve and eventually construct the effectual and robust approach. The purpose of this paper is to facilitate the managers for benchmarking the MHS alternatives operating under similar module via robust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…The authors found that elevated outcomes from the system can be achieved by strategically responding towards dominating measures, barriers etc., under the said system (Sahu et al , 2017). Analysis and streamlining system barriers under real-world scenario are complex and can be cracked by examining causal and effect relationships among them.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that elevated outcomes from the system can be achieved by strategically responding towards dominating measures, barriers etc., under the said system (Sahu et al , 2017). Analysis and streamlining system barriers under real-world scenario are complex and can be cracked by examining causal and effect relationships among them.…”
Section: Discussionmentioning
confidence: 99%
“…e highest nitrate value was observed at site P1, while site P2 shows the least value. Nitrate, a compound of nitric acid, is the most highly oxidized form of nitrogen found in aquatic environment [29][30][31]. It is an essential nutrient for many photosynthetic autotrophs and in some instances, functions as a growth-limiting nutrient.…”
Section: Total Organic Carbonmentioning
confidence: 99%
“…• Statement 2.2.7: grey theory imparts probabilistic thinking, which can define necessary outcomes for the system (Sahu et al, 2017;Liu, Zeng, Jiefang, Naiming and Yingjie, 2015).…”
Section: Second Phase Of the Methodologymentioning
confidence: 99%